2012
DOI: 10.1186/1471-2458-12-99
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in the uptake of breast and cervical cancer screening in Italy: a cross sectional study

Abstract: BackgroundBreast and cervical cancer screening are widely recognized as effective preventive procedures in reducing cancer mortality. The aim of this study was to evaluate the impact of socioeconomic disparities in the uptake of female screening in Italy, with a specific focus on different types of screening programs.MethodsA cross-sectional study was conducted using data from the 2004-2005 national health interview survey. A sample of 15, 486 women aged 50-69 years for mammography and one of 35, 349 women age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
108
4
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 40 publications
(50 reference statements)
21
108
4
10
Order By: Relevance
“…In a recent Italian study, education and occupation were positively associated with breast and cervical cancer screening (Damiani et al, 2012). Previous Korean studies have also reported that cancer screening rates are associated with age and socioeconomic status such as education level and household income (Kwak et al, 2005;Myong et al, 2012;.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent Italian study, education and occupation were positively associated with breast and cervical cancer screening (Damiani et al, 2012). Previous Korean studies have also reported that cancer screening rates are associated with age and socioeconomic status such as education level and household income (Kwak et al, 2005;Myong et al, 2012;.…”
Section: Discussionmentioning
confidence: 95%
“…The findings can also explain by the fact that the study hospital serves women mostly at low socioeconomic and educational level. Damiani et al (2012) determined that among women who attended screening, those with lower levels of education and lower occupational classes were more likely than more advantaged women to attend organized screening programs rather than being screened on the basis of their own initiative. Perry (2001) emphasized that younger women are more likely to seek contraceptive advice from either general practitioner or the practice nurse, and this should be used as an opportunity to promote smear testing and offer opportunistic screening, if appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…To further reduce the burden of this cancer, vaccination against HPV infection has recently been introduced in Sweden and other western countries. However, socioeconomic disparities, and physical, and social characteristics may influence health-related behaviors, screening behaviors and health conditions in Sweden [2,3] and other countries [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%